Assessment of Pullulan, a Microbial Polysaccharide, as a Matrix for Senotherapeutics Delivery - Ramona-Daniela Pavaloiu; Fawzia Sha’at; Corina Bubueanu; Maria Petrescu; Claudia Sevcenco (Chemistry Proceedings, 2023)
This study’s objective was to assess pullulan, in the form of pullulan acetate, as a matrix for senotherapeutics delivery. Polymeric nanoparticles loaded with various senotherapeutics (metformin, quercitin, kaempferol, curcumin, and luteolin) were prepared via nanoprecipitation or double emulsion methods using pullulan acetate as a biodegradable polymeric matrix. Quercitin, kaempferol, curcumin, and luteolin nanoparticles showed good yield (<70%), satisfactory values of entrapment efficiency (<60%), and nanometric sizes ranging between 205 and 270 nm, with narrow dispersity and good stability at 4 °C. The formulations demonstrated that pullulan showed great potential for producing nanoparticles with application in senotherapeutics delivery.